Rola UNESCO w ochronie dóbr kultury i zasobów przyrodniczych - Stankiewicz, Wojciech (Przegląd Politologiczny, 2018)
The topic is organized in such a way as to allow the circumstances of the establishment of UNESCO, its legal foundations, and the expansion of its activities over the years to be presented. The presentation of successive conventions that have been passed demonstrates how UNESCO’s scope of interests has been expanding to keep up with the changing world. In the analysis of successive activities and programs conducted under the auspices of UNESCO, and the attempts taken to counter the threats for the preservation of cultural and natural assets, the significance of the organization in the area of the protection of world heritage is assessed.